Formation of Socio-Cultural Identity in Multicultural Education - Iryna Sokolova (Pedagogical Discourse, 2012)
This article highlights the problem contexts of socio-cultural identity structure researching. The peculiarities of national, European and ethnic types of identity are analyzed. Socio-cultural identity is proved to be an expression of human’s self-realization in intercultural space that realizes its own involvement into a socio-cultural, European, ethnic community. The specific process of creating socio-cultural identity in multicultural education is analyzed. Theoretical principles, content and levels of multicultural education (ethnic, civic and global) are determined.